Topology hiding routing based on learning with errors. (25th March 2020) - Wan, Shaohua
Abstract: The protocol of onion routing constitutes the underpinning of Onion Routing network for anonymous communication. However, since the main idea behind such protocol is to hierarchically peel the IP head and decode each crypted routing address, the topology with regards to path length or long‐term direction cannot be preserved. Owing to topology exposure, lots of attacks such as denial of service and differential flow analysis can be effectively conducted to violate the security of it. Moreover, considering that the path should be constructed by a sender in advance, onion routing is infeasible to be transplanted to ad hoc networks, let alone other defects such as heavy burden about computational complexity and package length. In this paper, a topology‐hiding routing protocol is proposed to address most of the aforementioned problems recurring to homomorphic learning with errors. Security analysis illustrated that nothing but only the IPs of adjacent hops will be revealed to any router. Also the computational complexity on sender side as well as the package length outperforms those of traditional onion routing algorithm in view of comparative simulation.